Pengaruh Mutu Pelayanan Terhadap Kepuasan Pasien Poliklinik Umum Di RSU Bethesda Gunung Sitoli - Alfred Solidaritas Telaumbanua; Deli Theo; Juliandi Harahap (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2024)
Quality is one of the important elements in every health service. Therefore, in providing health services for the community, health service providers must always maintain the quality of services provided. The purpose to be achieved in this study is to analyze the factors that affect the quality of health services on patient satisfaction of the General Polyclinic at Bethesda Gunungsitoli General Hospital. This type of research uses a descriptive analytical survey with a cross sectional design. The population in this study was all patients who came for outpatient treatment at the General Polyclinic at Bethesda General Hospital Gunungsitoli approximately 2235 visits to take smpel using the Accidental sampling method.While the sample amounted to 100 people. Data analysis was carried out by univariate, bivariate and multivariate analysis. Based on the results of the chi-square test, it is known that the incidence of hypotension affects Tangible, Responsiveness, Reliability, Assurance and Empahaty p = 0.000, meaning that there is Tangible, Responsiveness, Reliability, Assurance and Empahaty to patient satisfaction. From the results of multivariate analysis, it is known that the most influential variable in this study is the Responsiveness variable with an OR value of 15,104. The conclusion in this study is that responsiveness is the dominant factor affecting patient satisfaction at the General Polyclinic at Bethesda General Hospital Gunungsitoli. To be able to improve the quality of services that must be improved, especially security and comfort guarantees for patients such as: completing patient administration, responding quickly to patient complaints, providing drugs quickly and precisely, providing information and quick response in handling patients to be improved to create a patient satisfaction that becomes patient satisfaction at the General Polyclinic at Bethesda General Hospital Gunungsitoli.